Analysis of Lean Manufacturing and Agile Manufacturing Implementation to Reduce Waste and Improve Productivity in Crankshaft Repair Production (Case Study: PT. Intidaya Dinamika Sejati – Jember) - Syahrul Ardiansyah; Rony Prabowo; Surjo Hadi (Jurnal Teknologi dan Manajemen, 2026)
This study aims to analyze the implementation of Lean Manufacturing and Agile Manufacturing in reducing waste and increasing productivity in the crankshaft repair production process at PT. Intidaya Dinamika Sejati – Jember. Value Stream Mapping (VSM) and Process Activity Mapping (PAM) methods are used to identify non-value-added activities. Root Cause Analysis, Pareto Diagram, and Fishbone Diagram are employed as supporting tools to analyze the main causes of waste. Agile Manufacturing is examined through the aspect of production flexibility. The results show that the dominant waste involves waiting time. After the implementation of improvements, there was an increase in production efficiency,  and an improvement in process lead time. The integration of Lean and Agile Manufacturing has proven effective in enhancing the company's operational performance.